Transcalvarial and Transdural Involvement of Skull Actinomycosis with Recurrence - Kramadhari Harshith; Krishnan Nagarajan; Andi Sadayandi Ramesh; Debasis Gochhait (Indian Journal of Neurosurgery)
Actinomycosis is caused by anaerobic gram-positive bacteria of Actinomyces genus, generally found as commensals in the human body and infection occurs when the immune system is compromised. We present the case of a 35-year-old diabetic woman, who presented with headache and sudden onset of left-sided weakness apart from scalp swelling, which on imaging showed transcalvarial transdural involvement, and subsequent surgical debridement and histopathologic analysis confirmed actinomycosis. Follow-up showed recurrence of the lesion at the same site following a period of remission. Calvarial involvement of actinomycosis is rare and can mimic even neoplastic or malignant lesions, hence requiring prompt diagnosis, treatment with surgery, and long-term antibiotic treatment to prevent complications.